Trading statement releases and the subsequent price formation process : evidence from the JSE - Cata, Olwethu (Department of Finance and Tax, 2015)
The relationship between unexpected earnings and security returns subsequent to earnings announcements is widely documented in international studies (e.g., Ball and Brown, 1968; Beaver, 1968; Beaver, 1974; Foster, Olsen and Shevlin, 1984). However, much of this research has been conducted in developed stock markets, with only a handful of studies focused on the JSE (e.g., Knight, 1983; Kornik, 2005; Murie, 2014). By drawing lessons from prior international and local evidence, and for the first time on the JSE, an investigation is conducted focusing on the entire price formation process from trading statements releases to the announcements of actual earnings. Adopting the returns based unexpected earnings measures of Foster, Olsen and Shevlin (1984) and van Rensburg's (2002) two factor APT specification to account for systemic risk, this study finds trading statements to contain new and significant information as evidenced by the presence of significant abnormal returns on their publication date. In addition, and consistent with semi-strong form market efficiency, no relationship is found between the sign and magnitude of unexpected earnings and the cumulative abnormal returns in the period subsequent to trading statement releases and preceding earnings announcement. Examining returns in the post-trading statement release period, the study found no evidence of statistically significant abnormal returns drift for good and bad news portfolios classified according to the (-1, 0), (-1, 1) and (0, 1) unexpected earnings models and that classified according to the trading statement sign. Consistent with prior South African studies, the publication of earnings is found to be a noteworthy market event to which investors react. In addition, the sign and magnitude of the initial response to unexpected earnings was found to exhibit a significantly positive relationship with cumulative abnormal returns over the (2, 60) day period subsequent to earnings announcements, representing a stark violation of semi-strong form market efficiency. Furthermore, the negative relationship between CARs in the (-1, 1) day period surrounding earnings and the post-trading statement drift postulated by Das, Kim and Patro (2007) does not appear to apply on the JSE. Examining returns in the (2, 60) day post earnings announcement period, the study found evidence of predictable returns drift but that the magnitudes of the CARs were not statistically significant over this period.